Problem and Solution of the Chinese Art Market - Li , Jialiang (Transactions on Economics, Business and Management Research, 2024)
Art market plays an important role in China society. The market benefits China’s economic, and brings a new investment approach; improves national overall aesthetic quality, and gives more people opportunities to access to art; propagates traditional Chinese culture, and expands the influence of traditional and modern art. Although Chinese art market develops rapidly and has extreme influence to the whole society, itself faced a lot of problems which might hinder the development of Chinese art market. This paper analysis some of the most important problems and provides solution. To be more specific, problems include information asymmetry, lacking access to international market, and lacking a valuation system. Solutions are reducing information asymmetric, connect international market and domestic market more closely, and make an evaluation system. This study gives important suggestions to Chinese art market participants, helps to rectify the problems of the market, and facilitate healthy develop of Chinese art market.